The extent of the commitment of audit offices accredited to the Central Bank of Libya to assess the ability of Libyan commercial banks to continue in accordance with International Auditing Standard 570 - مصباح رزق الله, رزق الله; مصطفى جمعة, دلال (Dirasat in Economics and Business, 2024)
The main objective of this study is to identify the extend of، external auditing offices certified by the Libyan Central Bank commitment to evaluate the going concern of the Libyan commercial banks according to IAS 570 focusing on auditors' commitment to financial indicators، financial failure indicators، and audit evidence gathered. In order to achieve these objectives، the analytical descriptive approach was used and 97 questionnaires was distributed to auditing offices، and 60 questionnaires were retuned and analyzed. Based on descriptive statistics and one sample independence test the data was analyzed and used to test the hypotheses. The findings revealed that external auditing offices which are certified by the Libyan Central Bank have commitment to evaluate the going concern of the Libyan commercial banks according to IAS 570 and particular they are committed to use financial indicators، financial failure indicators، and gather audit evidence in the assessment of going concern of Libyan commercial banks.